The Printing Dress - Small, Sheridan Martin; Roseway, Asta (International Symposium on Wearable Computers, 2011)
You are probably familiar with the old saying, “You are what you eat” but how about, “You are what you tweet?” What if this concept were incorporated into garments of the future? Would you censor yourself, knowing you would reveal your statements to the world around you? The “Printing Dress” is an artistic piece that explores the notion of wearable text and its potential impact on the future of fashion, as well as our social identity. Built almost entirely of paper, the dress enables the wearer to enter “thoughts” on to its fabric and wear them as public art. By selecting materials and technologies that draw on the past, present, and future of communication media, we encourage viewers to reflect on the path that has brought us to ubiquitous digital communication and to contemplate its forward evolution. "Best in Show" ISWC 2011 Design Exhibition "Best Concept" ISWC 2011 Design Exhibition